5G-based networking in unlicensed spectrum - Min XU; Nan HU; Nan LI (Dianxin kexue)
Due to the growing demand for mobile communication services, the shortage of licensed frequency bands is becoming more and more obvious. Therefore 5G networks begin to consider deployment in the unlicensed spectrum, that is, to employ the NR protocol in unlicensed spectrum to provide access services. The main challenge of 5G networking in the unlicensed spectrum is to support LBT mechanism considering 5G new technical features and thus to guarantee fairness with existing systems as well as efficient spectrum sharing, the impact of LBT on 5G networking in the unlicensed spectrum was analyzed, the relevant standardization progress and challenges was summarized. Feasible and innovative solutions were proposed for some key technical issues to minimize the impact of LBT failure and thus to ensure the performance of 5G networking in the unlicensed spectrum.